Effect of perfusion index on oxygen reserve index accuracy in estimating arterial oxygen tension in anesthetized dogs: Data reanalysis - Francesca Zanusso; Luca Bellini (PLoS ONE, 2025)
Multi-wave CO-oximetry, utilizing the oxygen reserve index (ORi), estimates arterial partial pressure of oxygen (PaO2) in mild hyperoxemia, between 100 and 200 mmHg, and concurrently quantifies local perfusion at the measurement site using the perfusion index (PI). This study explores how variations in PI influence the accuracy of ORi in estimating PaO2 in anesthetized dogs. Data from 37 mechanically ventilated dogs were retrospectively reanalyzed using a different approach. ORi and PI values were collected using a CO-oximeter. The data were categorized into four groups based on PI quartiles. In each group, the relationship between ORi and PaO2 was assessed using linear regression analysis, and the area under the receiver operating characteristic curve (AUROC) investigated the diagnostic performance of ORi in detecting PaO2 >  150 mmHg. Strong relationships between ORi and PaO2 were observed in groups with PI values <  2 (r2 ≥  0.63). The AUROC of ORi for identifying PaO2 > 150 mmHg decreased with PI >  2 compared to lower values (0.76 vs >  0.88). In this study, PI values >  2 negatively impacted ORi’s ability to estimate PaO2, likely due to fluctuations in blood flow perfusing the measurement site. The results of this study suggests that consideration of the PI value is essential when titrating oxygen therapy using ORi in anesthetized dogs.